Peran Kepemimpinan Adat Dalam Tata Kelola Pemerintahan Desa Studi Kasus Desa Tanjung Koto Kampar Hulu - Lili Suryani; Sujianto Sujianto; Nurmala Sari; Lilis Wahyuni; Latip Latip (Journal of Innovative and Creativity, 2025)
This study aims to analyze the role of traditional leadership in village governance in Tanjung Village, Koto Kampar Hulu District, Riau. Tanjung Village is an indigenous village that upholds the principle of Tali Bapilin Tigo as a foundation of unity between customary law, religion, and government. The study employed a descriptive qualitative approach using observation, interviews, and documentation. The results reveal that traditional leadership plays a crucial role in conflict resolution, decision-making, and strengthening the legitimacy of village governance. Although village governance is conducted democratically, the presence of traditional leaders from the four clans (Bomo, Melayu, Piliang, and Pitopang) remains a primary reference in social and political life. A comparison with other indigenous villages in Indonesia shows that Tenganan Village (Bali) is dominated by customary law, Minangkabau Nagari emphasizes the integration of customary law and Islam, while Tanjung Village represents an integration of customary law, religion, and government. This study highlights that traditional leadership can synergize with formal democracy, though challenges remain in administrative governance and village economic development